Zakat.X.kit - Adanan, Siti Azrina; Saidin, Amilia; Bustamam, Khair Syakira; Abdullah Sani, A'ieshah; Mamat, Siti Nurulhuda (2020)
Zakat.X.Kit is a mobile application (apps) that provides a platform for users to explore basic and extended zakat knowledge. This apps was initiated due to lack of awareness of zakat knowledge among youngsters, especially students in higher learning institution. Thus, the objective of this zakat kit is to enhance the level of zakat knowledge through attractive virtual interactive teaching method by providing notes, tutorial, educational games and online quizzes. It is a pioneer of its kind in zakat education for teaching and learning purposes. Users of the zakat kit will learn about various types of zakat wealth which includes traditional and modern wealth as well as principles and conditions of zakat obligation. Zakat.X.Kit able to attract potential users in exploring the zakat information and in turn will contribute to an increase in the number of zakat payers. Further, this apps can benefit various level of users, not only to the youngsters but also to public as a whole.